Evaluasi atas Pelaksanaan Sistem Informasi Akuntansi dalam Menciptakan Pengendalian Intern Yang Efektif Atas Mutasi Persediaan Barang Studi Kasus pada PT. Cahaya Buana Kemala - Muanas, Muanas (Jurnal Ilmiah Ranggagading (JIR), 2005)
The research is done to evaluate the implementation of accounting information system on stock mutation covering operational technique through stock data input in the administration. The existence of various differentials in the goods physically compared to stock administration data is the problem on which the research is based. The focus or the target is the analysis of the factors that trigger the problems above: whether the accounting information system itself is not effective or whether the process of the implementation deviates from the determined system. Key words: Accounting Information system; Internal control; Inventory